CHARACTERISTICS OF MONSOON AND RAINFALL PATTERN AT UMIAM, MEGHALAYA - Satapathy, K.K.; Jena, S.K.; Choudhury, D.Das (Journal of Soil and Water Conservation, 2022)
Rainfall analysis with advanced statistical methods using computer programming and computer software bring out many features which can be directly used for crop planning, land use, water management, pisciculture and floriculture planning etc. The analysis of 15 years (1983-1997) rainfall and evaporation data of Umiarn, Meghalaya has been done for determining the characteristics of rainfall, onset olf effective monsoon etc.